2022
DOI: 10.1186/s12872-022-02669-8
|View full text |Cite
|
Sign up to set email alerts
|

Challenges faced by patients with dyslipidemia and systemic arterial hypertension in Brazil: a design of the patient journey

Abstract: Background and objective Non-communicable diseases like systemic arterial hypertension (SAH) and dyslipidemia are poorly studied in terms of patient journey aspects. This semi-systematic review provides evidence synthesis for the management of SAH and dyslipidemia in Brazil and also discusses challenges faced by patients at the local level along with a suggested care approach by local experts. Methods A semi-systematic review using both structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Statins are recommended by guidelines to intensively reduce LDL-cholesterol in people with previous manifestations of ASCVD however previous studies had shown that recommended LDL-cholesterol goals were seldom attained by Brazilian patients. 6 , 15 , 16 , 23 , 24 The findings of this study performed in a broad sample of patients from different Brazilian regions visited by CHW in both rural and urban areas, indicate that absence or inadequate statin use may explain the latter. In addition, subjects reported low use of combination therapy with ezetimibe and no use of PCSK9 inhibitors, medications that reduce not only LDL-cholesterol but prevent ASCVD events.…”
Section: Discussionmentioning
confidence: 79%
“…Statins are recommended by guidelines to intensively reduce LDL-cholesterol in people with previous manifestations of ASCVD however previous studies had shown that recommended LDL-cholesterol goals were seldom attained by Brazilian patients. 6 , 15 , 16 , 23 , 24 The findings of this study performed in a broad sample of patients from different Brazilian regions visited by CHW in both rural and urban areas, indicate that absence or inadequate statin use may explain the latter. In addition, subjects reported low use of combination therapy with ezetimibe and no use of PCSK9 inhibitors, medications that reduce not only LDL-cholesterol but prevent ASCVD events.…”
Section: Discussionmentioning
confidence: 79%
“…Brazil ranks first in the number of articles published on this topic. This may be associated with the high incidence of hypertension in the country and the low cost of exercise treatment ( 25 ). China follows closely in third place, which may also be credited to the high incidence of hypertension and the popularity of traditional Chinese practices such as Baduan Jin and Tai Chi ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were used in this review, with minor modifications to fit within the scope of this study. The evidence was mapped using MAPS (Mapping the Patient Journey Towards Actionable Beyond the Pill Solutions) methodological approach [ 18 , 21 ]. The mapping strategy was divided into six steps: (1) developing a comprehensive search strategy; (2) establishing the inclusion and exclusion criteria; (3) screening and shortlisting; (4) supplementing with additional and/or local data; (5) data extraction and synthesis; and (6) evidence mapping.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, a national survey that mapped patient journeys in the Saudi population in 2005 reported > 1200 participants to be hypertensive with less than half of them being aware, receiving treatment, and having their BP controlled [ 17 ]. However, the studies reporting patient journeys in the following years were region-specific individual studies done at different times [ 18 ]. This may not provide an accurate estimate across all the journey touchpoints within the Saudi population who already have varied cultural norms and behavior towards CVD management [ 19 ].…”
Section: Introductionmentioning
confidence: 99%